2006
DOI: 10.1051/vetres:2005051
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cytokine expression in milk somatic cells during intramammary infections withEscherichia coliorStaphylococcus aureusby real-time PCR

Abstract: -The expression of inflammatory cytokines, including interleukin (IL)-6, IL-8, IL-12, granulocyte macrophage-colony stimulating factor (GM-CSF), tumor necrosis factor (TNF)-α, and interferon (IFN)-γ, by milk somatic cells was characterized by real-time polymerase chain reaction (PCR) in dairy cows experimentally challenged with either E. coli (n = 8) or S. aureus (n = 8). The mRNA abundance of a target gene was calibrated with that of a reference gene (β-actin) and expressed as fold of induction over the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
102
1
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(120 citation statements)
references
References 27 publications
15
102
1
2
Order By: Relevance
“…Possibly, in these sows there may be abundant and regulated release of anti-inflammatory mediators [40,53], limiting the production of the inflammatory cytokines. However, in accordance with our results, previous studies in cows have shown a significant increase in the proinflammatory cytokines at the level of both mRNA [33,37] and protein [6,11,26,32,45,48,54] in either mammary tissues or milk collected from the infected glands following intramammary inoculation with E. coli. The results here indicate that the development of clinical symptoms of coliform mastitis in the sow is associated with a locally increased proinflammatory cytokine production in response to intramammary E. coli infection.…”
Section: Discussionsupporting
confidence: 93%
“…Possibly, in these sows there may be abundant and regulated release of anti-inflammatory mediators [40,53], limiting the production of the inflammatory cytokines. However, in accordance with our results, previous studies in cows have shown a significant increase in the proinflammatory cytokines at the level of both mRNA [33,37] and protein [6,11,26,32,45,48,54] in either mammary tissues or milk collected from the infected glands following intramammary inoculation with E. coli. The results here indicate that the development of clinical symptoms of coliform mastitis in the sow is associated with a locally increased proinflammatory cytokine production in response to intramammary E. coli infection.…”
Section: Discussionsupporting
confidence: 93%
“…IRF3 activation is responsible for the expression of IFN-β and IFN inducible genes (e.g IP10, glucocorticoid-attenuated response gene 16). The up-regulation of these two transcription factors (NF-κB and IRF3) in the TLR4 signaling pathway in MAC-T cells supports the findings of several studies characterizing cytokine production by the mammary gland following bacterial infections [4,30] and thus confirming the ability of the mammary gland to mount a robust innate immune response to these infections.…”
Section: Discussionsupporting
confidence: 83%
“…Available lines of evidence indicate that bovine mammary epithelial cells respond to bacterial lipopolysaccharide and other microbial products by producing proinflammatory cytokines required to combat invading pathogens [4,7,17,30,32,38]. Other epithelial cell types (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, during mastitis PMN far outnumber macrophages by several orders of magnitude, and can therefore be major sources of cytokines like TNF-α. It was recently demonstrated by real-time PCR that mRNA expression of TNF-α, IL-6, IFN-γ, IL-8 and IL-12 was up-regulated in milk PMN following experimental intramammary injection of either E. coli, Staphylococcus aureus or S. aureus α-toxin [3,24,37,38]. Combined with the results from the present study it would appear that increased mRNA expression in milk PMN correlates with cytokine secretion.…”
Section: Discussionsupporting
confidence: 82%